Multi-Slice Computed Tomography Analysis in Patients Undergoing Transcatheter Aortic Valve Replacement – Impact of Workflows on Measurement of Virtual Aortic Annulus and Valve Size - Piayda, Kerstin; Hellhammer, Katharina; Veulemans, Verena; Afzal, Shazia; Klein, Kathrin; Berisha, Nora; Leuders, Pia; Erkens, Ralf; Kirchner, Julian; Heidari, Houtan; Kelm, Malte; Antoch, Gerald; et al. (Frontiers in Cardiovascular Medicine, 2022)
Exact and reliable measurements of anatomical dimensions in pre-procedural multi-slice computed tomography (MSCT) scans are crucial for optimal valve sizing and clinical results of transcatheter aortic valve replacement (TAVR). This study aimed to investigate interrater reliability between routinely used workflows for pre-procedural analysis. MSCT scans of 329 patients scheduled for TAVR were analysed using both a 3mensio and SECTRA IDS7 platform. The results were retrospectively compared using the intraclass correlation coefficient revealing excellent correlation in analysis of simple diameters and poor correlation in the assessment of more complex structures with impact on calculated valve size.